Analisis Pengaruh Variasi Jumlah Tumbukan Pada Campuran Asphalt Concrete Wearing Course (AC-WC) Beraspal Buton Terhadap Nilai Karakteristik Marshall - Ayu Saraswati; Andi Makkawaru Isazarni Jassin; Sri Jayani Syafitri (Sultra Civil Engineering Journal (SCiEJ), 2026)
The quality of roads in Indonesia is greatly influenced by the type of asphalt and the way it is compactioned. One of the important things in the Asphalt Concrete Wearing Course (AC-WC) mixture is the frequency of impact during compaction, which has a direct effect on Marshall characteristics such as stability and flow. This study aims to assess the impact of variations in the number of impacts (2×25, 2×35, 2×50, 2×75, and 2×85) on Marshall parameters and determine the optimum asphalt content (OAC). The main issue is how much influence impact the impact variation has on the Marshall parameters and the KAO value. The results showed that the variation in the frequency of the collision affected all Marshall parameters. The best conditions were found at 2×75 impacts, which increased the density, stability, and Marshall Quotient values, while VIM and VMA decreased, and the flow remained within limits. This suggests that the amount of impact during compaction is critical to the quality of the mixture. The optimum asphalt content was recorded between 6.00%-6.50% with small variations (±0.50%). A collision frequency of 2×75 is recommended as an ideal condition as it provides a balance between Marshall parameters and the need for optimal asphalt grades